An ecological and ecotoxicological perspective on fine particulate organic matter in streams. (3rd December 2015) - Bundschuh, Mirco; McKie, Brendan G.
Summary: Fine particulate organic matter (FPOM) provides a key longitudinal link within stream networks, and is the predominant food source for filter‐ and deposit‐feeding invertebrates, collectively classified as 'collectors'. Organisms involved in producing and using FPOM are sensitive to chemical and other anthropogenic stressors, but information on such impacts, and on FPOM dynamics in general, is limited. Here, we review information on the ecological role of FPOM in streams, and discuss potential impacts on FPOM dynamics of organic and inorganic chemical stressors, including metals and pesticides. Emphasis is placed on faecal particles produced within the leaf‐litter processing chain. Key biological factors controlling the resource quality of FPOM for collectors include the identity of the invertebrates producing FPOM, and the nutritional quality of their food resources. FPOM nutrient content is also strongly influenced by microbial colonisation and activity, and FPOM processing rates are thus likely to be sensitive to the impacts of stressors affecting microbes, including nutrients and antimicrobial chemicals. The potential for FPOM to bind and subsequently transport chemical stressors is high, particularly for hydrophobic compounds, but the extent of such effects and impacts on collectors consuming contaminated particles has attracted only limited attention. Combining concepts and research approaches from ecotoxicology and basic stream ecology would facilitate development of a common integrated framework for understanding the role of FPOM, and assessing anthropogenic impacts on FPOM dynamics in stream networks.